Comparative Physiological and Transcriptome Analysis Reveal the Molecular Mechanism of Melatonin in Regulating Salt Tolerance in Alfalfa (Medicago sativa L.) - Li, Shuxia; Wang, Yuan; Gao, Xueqin; Lan, Jian; Fu, Bingzhe (Frontiers in Plant Science, 2022)
As a high-quality legume forage, alfalfa is restricted by various abiotic stresses during its growth and development. Melatonin is a multifunctional signaling molecule that involves in plant defense against multiple stresses. However, little is known about its downstream signaling pathway and regulatory mechanisms in salt stress of alfalfa. In this study, we investigated the protective effects and key regulatory pathways of melatonin on alfalfa under salt tolerance. The results showed that melatonin promoted the growth of alfalfa seedlings under salt stress, as demonstrated by higher plant height, leaf area, and fresh weight. Melatonin treatment resulted in an increase in the photosynthetic capacity and starch content of alfalfa. Moreover, melatonin decreased cell membrane damage and reactive oxygen species (ROS) accumulation by enhancing antioxidant defense activity under salt stress conditions. Transcriptome sequencing (RNA-seq) analysis revealed that melatonin mainly induced the transcription of genes involved in Ca2+ signaling (cyclic nucleotide gated channel, CNGCs; cam modulin/calmodulin-like protein, CAM/CMLs and calcium-dependent protein kinase, CDPKs), starch and sucrose metabolism (α-amylase, AMYs; β-amylase, BAMs; starch synthase, SSs and sucrose synthase, SUSs), plant hormone signal transduction (auxin/indole acetic acid protein, AUX/IAAs; ABA receptor, PYL4; protein phosphatase 2C, PP2Cs; scarecrow-like protein, SCLs and ethylene-responsive transcription factor 1B, ERF1B), and key transcription factors (C3Hs, MYBs, ERFs, and WRKYs). Specifically, we focused on starch and sucrose metabolism and plant hormone signal transduction pathways. The interactions between melatonin and other phytohormones occurred via regulation of the expression of genes involved in hormone signaling pathways. In addition, melatonin increased the contents of endogenous melatonin, auxin, gibberellic acid (GA3), salicylic acid, brassinosteroids, and ethylene, while decreasing the abscisic acid content under salt stress. In summary, this study established a regulatory network for melatonin-induced key signaling pathways and functional genes under salt stress and provided a theoretical basis for salt tolerance breeding in alfalfa.